engelompokkan manifestasi kutan pada COVID-19 - Nandya Dwizella; Nevristia Pratama (CV. Jasa Sukses Abadi, 2022)
COVID-19 pandemic has gone through for more than two years, and it has taking millions of lives and has given a catastrophic damage globally in almost every aspect of life. The disease that is caused by SARS-CoV-2 virus is a novel disease that attack respiratory system in a swift manner. Even though respiratory system is the main concern of the disease, in the nature of its own disease, COVID is a systemic inflammatory disease and easily could make a different type of the symptoms in any other system of the body, not limited to respiratory system. It also gives a cutaneous manifestation with a lot of different lesion, but not handled properly and being overlooked. Until now, there is no concrete report of manifestation of cutaneous in COVID-19, this is one reason why clinician kept getting overlooked and do not giving patient a thorough and comprehensive therapy. The importance of report in cutaneous manifestation in COVID-19 patient will make clinician easier to notice the manifestation and could help them to make a proper comprehensive therapy for patient. Giovani et al has proposed a group of cutaneous manifestation of COVID-19, characterized by its own lesion, the location, pathophysiology and incidence. This grouping of manifestation hopefully can help clinician to identify cutaneous manifestation in COVID-19.